Persepsi Petani Muda Terhadap Profesi Sebagai Petani di Kecamatan Bancak Kabupaten Semarang - Susanto, Budi (Journal of Integrated Agricultural Socio-Economics and Entrepreneurial Research (JIASEE), 2022)
Farmers' work is carried out in rice fields, fields, fields, and gardens which are usually the livelihoods of the villagers. Currently, most of the farmers' work force is managed by older farmers. Meanwhile, the younger generation is less interested in continuing their parents' farming. Youth prefer to try their luck in the city because agriculture is less promising for economic improvement, and agricultural land is decreasing. This causes the youth's view of agriculture to be increasingly limited and it becomes difficult for them to stay on the farm. This study aims to examine the perception of young farmers towards farmer's work, to examine the perception-forming factors and to assess the relationship between the perception-forming factors and the perception of young farmers to the farmer's work. The basic method used is descriptive analysis with survey techniques. The research location was determined purposively, namely Bancak District, Semarang Regency. The sample was determined using a multistage cluster random sampling technique, as many as 60 young farmers spread over three villages, namely Pacekelan Village, Ganggeng Village, and Paduroso Village. The data used are primary data and secondary data. The data analysis used category classes to determine the perception of young farmers towards work as farmers and Rank Spearman (rs) to determine the relationship between the factors that shape perceptions and perceptions of young farmers towards work as farmers. The results showed that there was a very significant relationship between the family environment and socio-culture with youth perceptions of farmer work at the 99% confidence level, at the 95% level there was a significant relationship between work interactions and the primary social environment with youth perceptions of farmer work, while Formal education, non-formal education, secondary social environment, and cosmopolitan have no significant relationship with youth perceptions of farmer work